Perancangan Alat Uji Speedometer Portable Berbasis Arduino Guna Menunjang Pengujian Kendaraan Bermotor Keliling - Budi Sulistyo, Aris; Widiangga Gautama, Nengah; Dwifa, M. Beny; Dewa Punia Asa, I Putu (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
The death rate on the highway is increasing every year. One of the factors that adds to the death toll on the highway is the driver of a motorized vehicle driving more than the permitted speed. Speedometer is an important device in vehicles related to safety factors, because a good driver always pays attention to the speed of the vehicle he is driving with the condition of the road or terrain traversed. Therefore, in the kir test according to article 53 paragraph (1) of the LLAJ Law, there is a speedometer testing section. However, the implementation of portable vehicle speed measurement has not yet been implemented. The purpose of this study was to produce a prototype of a portable motorized vehicle speed measuring instrument based on Arduino. The output of this prototype design was the result of the vehicle speed reading that was carried out during the roving test. The main components of the prototype consisted of the Arduino Uno Microcontroller as the main control system, proximity sensor as a reader, bluetooth HC-05 as a data sender to Android, an AMOLED LCD display and an Android application via a smartphone to display the speed reading results. The prototype test gives a slight difference in the results with the speedometer in the vehicle and the speed on the Muller Bem. In this case, the speed shown by the prototype is still within the permissible limits, namely -10% to +15% of the Muller Bem tool.